ANALISIS TEKNIS DAN FAKTOR PENDUKUNG KEBERHASILAN BUDIDAYA RUMPUT LAUT DI PERAIRAN ALOR BESAR - Tell, Yulianto (JURNAL AKUAKULTURA, 2020)
The area of Alor Besar Village is locations on the coast, but the people in the area have not utilized its territorial waters to conduct seaweed cultivation. The causative factor is the limited knowledge of the community about cultivation techniques and the unavailability of information on location points that meet the requirements for seaweed cultivation. Research on seaweed cultivation in Alor is also still minimal, but on the other hand, the potential of the Alor sea needs to be used to improve the welfare of the people around these waters. The purpose of this research is to provide recommendations for the feasibility of the location and to determine the appropriate cultivation method for seaweed cultivation. This study seeks to combine methods based on technical and non-technical aspects to analyze the feasibility of cultivating seaweed in Alor Besar. The results of the analysis show that the waters of Alor Besar are in the appropriate category and very suitable to be used as a location for seaweed cultivation. The meaning that if used properly, the waters of Alor Besar can generate economic value for the welfare of the people there. The cultivation methods that can apply to these waters are the floating and bottom stepping methods.